The Historical Evolution and Enlightenment of Marx’s View of Civil Society - Xin, Tong (International Journal of Social Sciences and Public Administration, 2024)
In-depth study of young Marx’s civil society theory has important academic and practical significance. In terms of academic theory, "civil society" is a red line that runs through the gradual formation of Marx’s materialist view of history. Clarifying the development vein of young Marx’s view of civil society and clarifying the connotation and characteristics of civil society is helpful to understand the focus of young Marx’s philosophical research, so as to grasp the evolution of his ideological history more carefully. In reality, it is of great significance to construct the road of socialist modernization governance with Chinese characteristics to absorb and draw on the theoretical essence which accords with China’s national conditions.